Self‐Powered Low‐Platinum Nanorod Alloy Monoelectrodes for Rain Energy Harvest. Issue 9 (30th July 2018) - Duan, Yanyan; Duan, Jialong; Zhao, Yuanyuan; Tang, Qunwei; He, Benlin
Abstract: Here self‐powered low‐platinum coated copper nanorod alloy monoelectrodes are designed to generate electricity from rain, assisted by poly(ethylene oxide)/polyaniline conductive adhesive. Arising from charging/discharging processes of the electric double‐layer pseudocapacitance at electron‐enriched monoelectrode/rainwater interfaces, the monoelectrode yields a current signal of several microamps under dripping simulated raindrops. By optimizing stoichiometric Cu/Pt ratio, dripping velocity, cation concentration, and cation species, the current outputs are maximized. Abstract : Rain energy harvest ! Self‐powered monoelectrodes from low‐platinum coated copper nanorod alloys have been eatablished to convert rain energy into electricity. Arising from charging/discharging processes of the electric double‐layer pseudocapacitance at electron‐enriched monoelectrode/rainwater interfaces, the monoelectrode yields a current signal of several microamps under dripping simulated raindrops.